Transforming programming education through a quiz-based mobile app: an innovation in formative learning for C++ - Ibrahim, Nur Syafikah; Suhaimi, Azrina; Kapi @ Kahbi, Azyan Yusra; Hasmy, Harshida; Ab Jabal, Mohamad Faizal (2025)
This study investigates the impact of a quiz-based mobile application on student engagement and learning outcomes in an introductory C++ programming course. The app featured topic-specific multiple-choice quizzes with instant feedback, unlimited reattempts, and automatic scoring. It was deployed to 301 undergraduate students for voluntary self-practice before formal assessments. Engagement data showed that 63% of students attempted the quiz for Topic 1, and 39% for Topic 2. Many students reattempted the quizzes multiple times, highlighting the application’s role as a selfpaced formative learning tool. A comparative analysis between students who used the app (“Answered” group) and those who did not (“Did Not Answer” group) revealed significant performance improvements. For Topic 1, app users scored an average of 25.16 compared to 22.36 for non-users (+2.80); for Topic 2, users averaged 26.51 versus 22.64 (+3.87). Independent samples ttests confirmed that these differences were highly significant (p < 0.0001), indicating a strong positive impact on learning outcomes. The app’s effectiveness is attributed to several pedagogical factors: realtime feedback to correct misconceptions, repeated practice that reinforces learning, and a low-stakes environment that promotes exploration and learning from mistakes. This innovation reflects a transformative approach to programming education by integrating mobile technology to foster learner autonomy and lifelong learning habits. It also contributes to educational research by demonstrating how mobile formative assessment tools can drive innovation in student engagement and academic achievement. Future work will focus on expanding content and incorporating personalized feedback mechanisms.